2015
DOI: 10.1111/pcmr.12380
|View full text |Cite
|
Sign up to set email alerts
|

Proteome characterization of melanoma exosomes reveals a specific signature for metastatic cell lines

Abstract: Exosomes are important mediators in cell-to-cell communication and, recently, their role in melanoma progression has been brought to light. Here, we characterized exosomes secreted by seven melanoma cell lines with varying degrees of aggressivity. Extensive proteomic analysis of their exosomes confirmed the presence of characteristic exosomal markers as well as melanoma-specific antigens and oncogenic proteins. Importantly, the protein composition differed among exosomes from different lines. Exosomes from agg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
135
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 132 publications
(142 citation statements)
references
References 38 publications
7
135
0
Order By: Relevance
“…[33][34][35] Apo-A1-CD63 presenting exosomes produced by 293T cells were loaded with miR-26a by electroporation and shown to be internalized by HepG2 cells via SR-B1 receptor-mediated endocytosis. The exosome-mediated delivery of miR-26a to HepG2 cells was further shown to upregulate miR-26a expression, where it downregulated key cell cycle proteins that arrested the cell cycle and inhibited cell proliferation.…”
mentioning
confidence: 99%
“…[33][34][35] Apo-A1-CD63 presenting exosomes produced by 293T cells were loaded with miR-26a by electroporation and shown to be internalized by HepG2 cells via SR-B1 receptor-mediated endocytosis. The exosome-mediated delivery of miR-26a to HepG2 cells was further shown to upregulate miR-26a expression, where it downregulated key cell cycle proteins that arrested the cell cycle and inhibited cell proliferation.…”
mentioning
confidence: 99%
“…Specimens were prepared as described previously (13). Mitochondria were quantified by counting the number per picture on at least 50 pictures per experiment (an average of 20 mitochondria per picture).…”
Section: Transmission Electron Microscopymentioning
confidence: 99%
“…When indicated, etomoxir (50 mmol/L) or trimetazidine (1 mmol/L) were added 24 hours after exosomes. Actin was stained with phalloidin as described previously (13).…”
Section: Cell Lines and Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…64 It was latter on reported that certain proteins were differentially expressed dependently on the melanoma cells from which the exosomes were analyzed, revealing a specific signature for metastatic cell lines. 65 In this way, in exosomes from patients with metastatic melanoma, MIA (Melanoma Inhibitory Activity) and S100B can be detected, therefore their quantification presents diagnostic and prognostic utility. 66 In 2015, Hoshino et al revealed that specific integrin expression in exosomes could be used to predict organ-specific metastasis.…”
Section: Exosomes As Biomarkersmentioning
confidence: 99%